Implementation of RFID tracking across the entire supply chain - Hinkka, Ville; Aalto-yliopiston perustieteiden korkeakoulu. Tuotantotalouden laitos (Aalto University publication series, ISSN 1799-4934, 2013)
Toimitusketjun laajuisen RFID-seurannan käyttöönotto.
Keywords: logistiikka; kauppa; seuranta; toimitusketjut; uppföljning; handel; logistik; leveranskedjor; supply chain management (SCM); supply chain integration; interorganisational information systems (IOIS); design science; Radio Frequency Identification (RFID); tracking; RDIF